Habilidades culinárias em estudantes universitários: existe uma associação com o sobrepeso e a obesidade? - Pelonha, Rafaela Nayara da Costa (2023)
Cooking skills (CS) are defined as an individual's confidence, attitude, and application of knowledge to perform culinary tasks. Developing these skills can improve the quality of the diet, as cooking at home can encourage the consumption of vegetables and reduce the use of ultra-processed foods, which can result in benefits to nutritional status. University students are faced with the difficulty of balancing academic activities, studies, social life and work, with little time to be dedicated to cooking. High consumption of ultra-processed foods is common during this period of life, which may be related to low levels of CS and the emergence of overweight/obesity, as observed in some studies. Therefore, it can be suggested that the development of CS in this population becomes essential as a health promotion measure. This study aimed to analyze the association between CS and overweight/obesity in university students. The methodology consisted of a descriptive, observational, and cross-sectional study, with data collected between October/2020 and March/2021 through an online form, with 822 undergraduate students from the Federal University of Rio Grande do Norte. For sociodemographic characterization, a questionnaire with 15 questions was applied and to characterize CS, the Brazilian Cooking Skills and Healthy Eating Questionnaire (BCSQ) with 7 scales was applied. Logistic regressions were used to assess associations of CS with overweight and obesity. Among research participants, 70.3% were female; with a median age of 23 years; 43.6% were overweight while 56.4% were not overweight. As for CS, 0.6% had low CS, 33.4% had medium CS and 65.9% had high CS. Overweight and obesity were shown in the bivariate analysis to be significantly associated with low levels of the CS scales of “cooking self-efficacy” and “self-efficacy in the use of fruits, vegetables and seasonings”. Logistic regressions demonstrated that living with other people and eating out were associated with greater odds of being overweight and obese. Sharing responsibility for preparing meals and high “self-efficacy in the use of fruits, vegetables and seasonings” were associated with lower chances of overweight/obesity. Therefore, the results suggest that CS can be explored in educational programs aimed at reducing overweight/obesity in these students by improving the quality of their diet. The study resulted in an article published in the journal “Nutrients” entitled “Low cooking skills are associated with overweight and obesity in undergraduates”.